At War For Perioperative Nurses - Panneton, Yves (Operating Room Nurses Association of Canada Journal, 2000)
Not only did soldiers fight the enemy on the front line of the Crimean war, they also fought infection once injured. The problem with infection was so serious, that the “cavalry” lead by Florence Nightingale took up the challenge to fight it. Her “arsenal” included what we now term sanitation, physiotherapy, and nutrition along with nursing care. As her “enemy” retreated, she laid down the foundation of modern nursing — 150 years ago!